Why was resistance to shorter‐acting pre‐emergence herbicides slower to evolve?. Issue 5 (20th February 2017) - Somerville, Gayle J; Powles, Stephen B; Walsh, Michael J; Renton, Michael
Abstract: BACKGROUND: Across several agricultural systems the evolution of herbicide resistance has occurred more rapidly to post‐emergence than pre‐emergence herbicides; however, the reasons for this are not clear. We used a new simulation model to investigate whether interactions between differences in order of application and weed cohorts affected could explain this historically observed difference between the herbicide groups. RESULTS: A 10 year delay in resistance evolution was predicted for a shorter‐acting residual pre‐emergence (cf. post‐emergence), when all other parameters were identical. Differences in order of application between pre‐ and post‐emergence herbicides had minimal effect on rates of resistance evolution when similar weed cohorts were affected. CONCLUSION: This modelling suggested that the historically observed lower levels of resistance to pre‐emergence herbicides are most likely to be due to the smaller number of weed cohorts affected by many pre‐emergence herbicides. The lower number of weed cohorts affected by pre‐emergence herbicides necessitated the use of additional, effective control measures, thereby reducing resistance evolution. This study highlights the advantages of applying multiple control measures to each weed cohort. © 2016 Society of Chemical Industry